Analisis Dampak Daya Apung Terhadap Benda di Lingkungan Sekitar pada Praktikum Pendidikan Ilmu Pengetahuan Alam - Hamna, Hamna; BK, Muh. Khaerul Ummah; Novianti, Desi; Aulia, Dina; Muliyani, Muliyani (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This research aims to analyze the impact of buoyancy on objects in the surrounding environment in the context of Natural Sciences (IPA) educational practicum. The research uses a qualitative approach with simple experimental methods to measure the effect of buoyancy on various types of objects based on density and volume. Data was obtained through direct observation during practicum involving the research team. Data analysis using descriptive analysis by summarizing and interpreting observational data related to object behavior. The research results show that buoyancy plays an important role in determining whether an object will sink, float or float in water. The main factors that influence buoyancy include the physical properties of the object, such as the density relative to the fluid, and the volume of the object submerged. These findings contribute to the research team's understanding of Archimedes' principle and its application in everyday life.